Σχεδιασμός και ανάπτυξη προϊόντος: εφαρμογή στη βιομηχανία συσκευασίας - Σταχούλη, Κωνσταντίνα (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Μηχανολόγων Μηχανικών, 2018)
This Thesis deals with the Product Design and Development Process and its application in a Packaging Industry. Initially, the basic information and the steps of the General Product Development Process are presented, which is carried out in all enterprises and is the process followed from the initial phase of conception of the idea of a product up to the final phase which is the objective, placing on the market. Then, I describe in detail the six stages of the General Development Process. In addition to this, I present an analysis of these stages, opportunities and the problems that arise in this process. After analyzing the product development process, we see that one of the main functions that are almost always at the heart of product development is Design. Because the function of the design plays a major role, if not the main role before the final production of the product, I then analyze extensively the product design process, the designer's tools, the multidimensional design problem and the design process in an enterprise . And for a better understanding of this process, which is an integral part of a company's flow, it follows the application of this process to an existing business. Then I will introduce the basic info for an industry where we will see the implementation of this process in practice, and this is in particular the Packaging Industry of Corrugated Board. After presenting the characteristics of the Packaging Industry and Corrugated Board Packaging, we will see in detail the implementation of the Product Design and Development Process within the business and tools used. Finally, I present three case studies in the Corrugated Board Packaging Industry to see how the product R & D process is being adapted to practice and what steps are being followed in practice, what is the challenge, what is the approach of the Design team and Development and the results of this.